Multi-level modeling: cornerstones of a rationale: Comparative evaluation, integration with programming languages, and dissemination strategies - Frank, Ulrich (Software and systems modeling, 2022)
This expert voice paper presents a comprehensive rationale of multi-level modeling. It aims not only at a systematic assessment of its prospects, but also at encouraging applications of multi-level modeling in business information systems and at providing a motivation for future research. The assessment is developed from a comparison of multi-level modeling with object-oriented, general-purpose modeling languages (GPMLs) and domain-specific modeling languages (DSMLs). To foster a differentiated evaluation, we propose a multi-perspective framework that accounts, among others, for essential design conflicts, different types of users, as well as economic aspects. Besides the assessment of the additional abstraction offered by multi-level modeling, the evaluation also identifies specific drawbacks and remaining challenges. Based on the results of the comparative assessment, in order to foster the adoption and further development of multi-level modeling, we discuss the prospects of supplementing multi-level modeling languages with multi-level programming languages and suggest possible dissemination strategies customized for different groups of users. The paper concludes with an outline of future research.